The Effectiveness of Blended Learning based on digital games in increasing students’ motivation toward learning mathematics - Al Kharusi, Ahmed; Al Abri, Mustafa; Al Badi, Amal; Al-Hadrami, Ahmed (Social Empowerment Journal, 2023)
This research is action research aimed to reveal the effectiveness of using blended learning based on digital games in increasing the motivation of grade-five students towards learning mathematics. The quasi-experimental method was used with thirty-eight grade-five students in Imam Al-Hassan bin Saeed Al-Sahtani Basic Education School for Boys (5-12) in the Sultanate of Oman. The study used two instruments; an educational program based on digital games and a scale of students’ motivation toward learning mathematics. The study found that there were statistically significant differences in favour of the post-motivation scale, in which the mean of the scale in pre-motivation scale was 2.73 and the mean of the post-motivation scale was 4.13. There was a difference of 1.4 in favour of the post-motivation scale. Considering the results of the study, the researchers recommended encouraging teachers to use blended education based on digital games and making various interactive activities for students through instructional digital games.